Dari Frekuensi ke Algoritma: Komodofikasi Konten Siaran Radio di Media Sosial - Iqbal Pratama Putra; Sabago Viesaasa; Ferry Darmawan (UPT Publikasi Ilmiah Unisba, 2026)
Abstract. This article examines the commodification of broadcast content at PRFM Bandung, a news radio station, within the social media ecosystem through the lens of the political economy of media. This approach is employed to analyze how power relations, particularly those driven by economic interests, shape the production and distribution of communication resources. Content transformation has become a strategic response by traditional radio media to generate new revenue streams amid the saturation of the conventional advertising market. This condition demonstrates that digital adaptation is not merely a technical process but also reflects a shift in the economic orientation of media management. Data were collected through digital observation and in-depth interviews with the media management. The findings indicate that the commodification of content, by repackaging audio broadcasts into visual content, represents a pragmatic strategy to attract advertisers. These findings confirm that, in order to maintain the company's cash flow and organizational sustainability, radio media must transform content into economic exchange value within the structure of platform capitalism. Furthermore, this phenomenon illustrates how economic relations and the power of digital platforms increasingly require radio broadcasters to adapt their content production and distribution strategies in response to the dynamics of the platform ecosystem. Abstrak. Artikel ini menganalisis praktik komodifikasi konten siaran pada radio PRFM Bandung sebagai radio berita dalam ekosistem media sosial melalui pendekatan ekonomi politik media. Pendekatan ini digunakan untuk membedah bagaimana relasi kekuasaan yang mencakup kepentingan ekonomi membentuk produksi dan distribusi sumber daya komunikasi. Transformasi konten dilakukan sebagai strategi media tradisional untuk membuka keran pendapatan baru di tengah jenuhnya pasar iklan konvensional. Kondisi tersebut memperlihatkan bahwa adaptasi digital tidak hanya bersifat teknis, tetapi juga merefleksikan perubahan orientasi ekonomi dalam pengelolaan media penyiaran. Data dikumpulkan melalui observasi digital serta wawancara mendalam dengan pihak manajemen media. Hasil penelitian menunjukkan bahwa komodifikasi konten melalui pengemasan siaran audio menjadi konten visual merupakan respons pragmatis untuk menarik pengiklan. Temuan ini menegaskan bahwa demi menjaga keberlangsungan arus kas perusahaan, media radio harus mentransformasi konten menjadi nilai tukar ekonomi dalam struktur kapitalisme platform. Fenomena tersebut memperlihatkan bagaimana relasi ekonomi dan kekuasaan platform menuntut perlunya adaptasi arah produksi dan distribusi konten media penyiaran radio.